2021
DOI: 10.1161/hypertensionaha.121.17788
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Blood Pressure Variability Increases Risks of Dementia and Cognitive Decline: A Meta-Analysis of Longitudinal Studies

Abstract: High blood pressure (BP) is considered as an important risk factor for cognitive impairment and dementia. BP variability (BPV) may contribute to cognitive function decline or even dementia regardless of BP level. This study aims to investigate whether BPV is an independent predictor for cognitive impairment or dementia. Literature searches were performed in MEDLINE, Embase, PsycINFO, CINAHL, and Web of Science to May 2021. Longitudinal studies that assessed the risk of dementia or cognitive impairment with BPV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 54 publications
(100 reference statements)
3
41
1
Order By: Relevance
“…The current investigation adds to ongoing work detailing relationships between BPV and AD. 6 , 10 , 11 , 13 , 16 - 18 , 38 In addition, patterns of CSF change were observed predominantly in APOE ε4 carriers, consistent with recent work relating BPV and APOE ε4 to other important markers of AD (e.g., medial temporal volume loss). 18 …”
Section: Discussionsupporting
confidence: 88%
“…The current investigation adds to ongoing work detailing relationships between BPV and AD. 6 , 10 , 11 , 13 , 16 - 18 , 38 In addition, patterns of CSF change were observed predominantly in APOE ε4 carriers, consistent with recent work relating BPV and APOE ε4 to other important markers of AD (e.g., medial temporal volume loss). 18 …”
Section: Discussionsupporting
confidence: 88%
“…These results align with similar studies, which have observed relationships between high BPV and cognition. 10 , 12 , 14 , 22 , 41 , 42 , 43 This relationship may be driven by long‐term hemodynamic instability and associated microvascular damage, atherosclerosis, and organ hypoperfusion, leading to increased white matter lesions, cortical infarcts, and other neuropathological contributions to cognitive dysfunction. 44 Confidence in these results is strengthened by the consistency of this pattern across ARV and VIM, with VIM indicating an association independent of BP level.…”
Section: Discussionmentioning
confidence: 99%
“…7 , 45 However, the current study demonstrates cognitive decline over time, a key criterion for AD 46 in a sample with multiple ethnic groups, an important knowledge gap in this relationship. 43 The lack of association between BPV with other cognitive measures is notable. It has been suggested that this association may be attenuated in healthier populations.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the CAN represents the neuroanatomical correlate of the brain-heart axis ( Silvani et al, 2016 ). Also, autonomic dysfunction can lead to blood pressure (BP) dysregulation ( Julius and Weder, 1989 ) which can contribute to cognitive impairment via cerebral hypoperfusion ( Forte et al, 2019b ; Jia et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%